2019
DOI: 10.1002/uog.20262
|View full text |Cite
|
Sign up to set email alerts
|

Early‐pregnancy events and subsequent antenatal, delivery and neonatal outcomes: prospective cohort study

Abstract: Objective To assess prospectively the association between pelvic pain, vaginal bleeding, and nausea and vomiting occurring in the first trimester of pregnancy and the incidence of later adverse pregnancy outcomes. Methods This was a prospective observational cohort study of consecutive women with confirmed intrauterine singleton pregnancy between 5 and 14 weeks' gestation recruited at Queen Charlotte's & Chelsea Hospital, London, UK, from March 2014 to March 2016. Serial ultrasound scans were performed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Zhu et al reported that women facing threatened miscarriage had a higher risk for major depressive and anxiety symptoms than those with stable pregnancies [ 50 ]. Al-Memar et al found that first-trimester vaginal bleeding was an independent risk factor for adverse obstetric outcomes [ 51 ], which might increase the risk of antenatal depression [ 52 ] and were also significant predictors of antenatal depression (adjusted OR 3.14) [ 53 ]. However, further studies are needed to determine the causes of the differences in the prevalence of depression during pregnancy and the interaction among antenatal depression, anxiety and somatic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al reported that women facing threatened miscarriage had a higher risk for major depressive and anxiety symptoms than those with stable pregnancies [ 50 ]. Al-Memar et al found that first-trimester vaginal bleeding was an independent risk factor for adverse obstetric outcomes [ 51 ], which might increase the risk of antenatal depression [ 52 ] and were also significant predictors of antenatal depression (adjusted OR 3.14) [ 53 ]. However, further studies are needed to determine the causes of the differences in the prevalence of depression during pregnancy and the interaction among antenatal depression, anxiety and somatic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of women were recruited after attending the Ultrasound Department or Early Pregnancy Assessment Unit of Queen Charlotte's and Chelsea Hospital. The cohort described in the present study has been reported on before in a previous study by our group evaluating the association between pelvic pain and/or vaginal bleeding occurring in the first trimester and the incidence of adverse pregnancy outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…These pretest scores were the key factor correlated with the outcomes for discomfort symptoms. Previous studies found that distress symptoms in the early trimester may increase the incidence of antenatal complications and affect postnatal symptoms and early motherinfant interaction (Al-Memar et al, 2019;Hakanen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%